Complications following intravesical bacillus Calmette-Guerin treatment for bladder cancer: a case series of 22 patients. Issue 10 (October 2015) - Pommier, J.D.; Ben Lasfar, N.; Van Grunderbeeck, N.; Burdet, C.; Laouénan, C.; Rioux, C.; Pierre-Audigier, C.; Meybeck, A.; Choudat, L.; Benchikh, A.; Nguyen, S.; Bouvet, E.; et al.
Abstract: Background: Intravesical bacillus Calmette-Guerin (BCG) therapy is an effective and widely used treatment for superficial bladder carcinoma. Local complications are frequent whereas systemic complications are rare but can be serious, and their management is not well known. Methods: We describe retrospectively the records of 22 patients treated in 3 infectious disease departments, for complications related to intravesical BCG therapy as treatment of bladder cancer. Results: All the patients were male, with a median age of 68 years (range 56–88). Complications occurred after a median of 5 instillations (range 1–11) and were observed within 24 h following BCG instillation for 14 patients. Common symptoms were fever ( n = 20), impaired general condition ( n = 14), and shortness of breath ( n = 7). Six patients had a systemic septic reaction leading to transfer into the intensive care unit for five of them. Lung infiltration was the most frequent presentation ( n = 11). Mycobacterium bovis was isolated from only two patients, but histology showed the presence of a granuloma in nine patients. Antimycobacterial treatment was initialized in 17 patients; the outcome was favorable in 16 patients, with a median length of symptoms resolution of 22.5 days (range 5–425 days). Eleven patients received corticosteroids in addition to specific treatment and had a more rapid improvement. One patient died with disseminated BCGitis proved by biopsy. Conclusions: Complications following intravesical BCG therapy are rare but can be severe and fatal. Histology seems to be the method that contributes most in confirmation of the diagnosis. Antimycobacterial therapy is effective, and probably more efficient when combined with corticosteroids, but the regimen and duration of the treatment are not standardized.